Manajemen Peserta Didik Dalam Rangka Pelayanan Pembelajaran Kepada Peserta Didik di SMANegeri 2 Karawang - Amiati, Tri Rara; Bakar, Abu; Waluyo, Kasja Eki (Jurnal Ilmiah Wahana Pendidikan, 2024)
Student management is an effort to organize and manage everything related to students, from the time they enter school until they graduate. This is done with various activities that have been determined by the school. This activity is important to help develop the potential of each student. Learning services to students are activities for teachers and schools to work together in a planned and sustainable manner in helping students to achieve their best potential in learning. This is done through various activities, such as designing appropriate learning, implementing interesting and effective learning, assessing learning progress, and providing necessary support services. This research aims to (1) find out student management planning at SMA Negeri 2 Karawang, (2) find out how student management planning works appropriate, (3) Knowing the organization carried out within the school coaching students to create good graduates, (4) Knowing what solutions to take if implementation is not in accordance with planning, (5) Knowing the parties involved in supervising the coaching, (6) Knowing the evaluation of student management at school. This study used descriptive qualitative method. In this case, the school carries out various service activity programs such as those related to planning the admission of new students, graduation, activities related to student development, and assessment of final results. Based on the results of interviews at SMAN 2 Karawang, researchers found problems related to self-development, placement of students, programmed activities both co-curricular and extra-curricular, as well as achievements achieved.